Reviving the Middle ages in Croatia (Fifteen-Year Anniversary Reports) - Vedriš, Trpimir (2009)
The study of the Middle Ages has played a crucial role in the study of Croatian history since its establishment as an academic discipline in the second half of the nineteenth century. This special interest in medieval history, however, had little in common with what is nowadays called “ medieval studies". Research in Croatian medieval history, similarly to other countries in nineteenth century Europe, was strongly linked to the process of "nation building". The author summarizes major trends in Medieval studies in Croatia during the second half of the 20th century with the special focus on the changes in the 1990s. Seeing the changes in the "epistemological configurations" in the field as positive ones, the author inquires the role of the alumni of the Department of Medieval studies at CEU in the process. Author concludes that a group of departmental alumni and current students make visible contribution to the modernisation and proliferation of medieval studies (mostly history) in Croatia.
Projekt MZOS
ENG